2008
DOI: 10.1007/s10552-008-9272-0
|View full text |Cite
|
Sign up to set email alerts
|

Case–control study of green tea consumption and the risk of endometrial endometrioid adenocarcinoma

Abstract: Green tea consumption may be associated with a lower risk of EEA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Of these studies, three were conducted in Japan [21-23] and two in China [16, 24]. It can be presumed that green tea was the main tea type consumed in these populations.…”
Section: Endometrial Cancermentioning
confidence: 99%
“…Of these studies, three were conducted in Japan [21-23] and two in China [16, 24]. It can be presumed that green tea was the main tea type consumed in these populations.…”
Section: Endometrial Cancermentioning
confidence: 99%
“…In a small cohort study following 254 women with diagnosed epithelial ovarian cancer over 3 years demonstrated that habitual green tea consumption caused a significant dose-dependent increase in survival rate (Zhang et al, 2004). Kakuta et al (2009) demonstrated a reduction in the risk of developing endometrial endometriod adenocarcinoma with habitual green tea consumption in a case-control study which included 437 women. A reduction in the risk for the development was observed for all subtypes of adult leukemia associated with the habitual high intake of green tea in a small case-control study involving 107 cases and 110 controls (Zhang et al, 2008).…”
Section: Observational Studiesmentioning
confidence: 99%
“…Yang et al 14 reported that regular intake of GT was shown to provide protection against the development of colorectal cancer in a large cohort of 69,710 Chinese women followed up for 2-3 years. Kakuta et al 22 demonstrated in a case-control study with habitual consumption of GT, which included 437 women, a marked reduction in the risk of developing endometrial endometriod adenocarcinoma. Many scientists have reported 13,23,24 that EGCG, epicatechin gallate, and epigallocatechin are the main constituents of GT extract that have cancer preventive activities, including growth inhibition of human cancer cell lines in cultures, induction of apoptosis, inhibition of tumor promotion and carcinogenesis in animal experiments, antimutagenic and antioxidant activities, inhibition of tumor necrosis factor-a release from cells induced by a tumor promoter, and modulation of gene expression.…”
Section: Introductionmentioning
confidence: 99%